Digital Logic and Asynchronous Datapath With Heterogeneous TFET-MOSFET Structure for Ultralow-Energy Electronics - Jo-Han Hung (IEEE, 2020)
The tunnel field-effect transistor (TFET) is a promising solution for high energy-efficient circuits. Based on the band-to-band tunneling (BTBT) condition, fast switching characteristic with a steep subthreshold swing (SS) in the ultralow-voltage operation is feasible. Our prior work has demonstrated that the SS and ON-state current can be improved without leakage current penalty through the usage of SiGe low-bandgap material in the epitaxial tunnel layer (ETL). ETL-TFET is highly compatible with the CMOS process, enabling heterogeneous integration of TFET and MOSFET in the same technology. In this work, the circuit performance of ETL-TFET and fully depleted SOI (FDSOI) MOSFET is evaluated and compared in terms of energy and delay metrics. By combining the advantages of TFET and MOSFET, heterogeneous pMOS-NTFET dynamic logic gates are proposed. The pMOS-NTFET-based logic gates demonstrate the lowest energy consumption than other realizations. Asynchronous datapath is leveraged to combat the timing variations in the ultralow-voltage region. A 20.9%–33.9% energy reduction is achieved compared with the conventional MOSFET counterpart.